REVITALIZATION OF ECOLOGICAL GREEN OPEN SPACE ON THE EDGE OF THE MAHAKAM RIVER IN SAMARINDA CITY (International Conference of Graduate School on Sustainability (ICGSS), 2020)
Samarinda City is the capital of East Kalimantan, which is geographically located on the Mahakam River banks. The development of Samarinda city is much influenced by the development of the Mahakam river corridor because the Mahakam river is very close to the life of the people of Samarinda. The Mahakam River divides Samarinda's city by forming a corridor with a city symbol, characteristics, and very potential to be developed, especially in the green open space corridor on the Mahakam River. Through the revitalization of green open space for the Mahakam river corridor, it is hoped that Samarinda City will have a city identity characterized by an ecological river corridor area. This discussion uses a qualitative descriptive method through the development of an ecological green open space planning concept. The development of the concept of ecological green open space planning is carried out through eco-spatial analysis based on the theoretical synthesis, the results of field observations to maintain its characteristics as a Mahakan Riverfront City.